(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
The article discusses the prevalence of periodontal diseases among 50 3rd- to 4th-year dental students studying at the Faculty of Dentistry of Samarkand State Medical University. The authors identified signs of inflammation in periodontal tissues, which is explained by the presence of dental anomalies and insufficient oral hygiene. The analysis of periodontal disease was observed in 85% of students, which explains the need for treatment and professional oral hygiene.